Estudo pré-clínico do galato de etila sobre a reatividade vascular, coagulação secundária e atividade agregante de plaquetas em ratos - Ramalho, Ricardo Cartaxo (2025)
Cardiovascular diseases (CVD) are established by the World Health Organization (WHO) as a group of conditions that affect blood vessels and the heart. CVDs represent the main cause of death globally, and Brazil is no exception. Data from DATASUS from 2022 indicate that approximately 27% of total deaths, that is, more than 400 thousand people, were caused by problems in the circulatory system in the year in question. Currently, the health system has several drugs used in CVD, but the quantity available for hemostatic diseases is still small. Therefore, it was decided to carry out a preclinical pharmacological analysis with derivatives of gallic acid, an important precursor of bioactive molecules, and verify their actions at the vascular level and hemostatic system, based on the possible vasorelaxant and antioxidant effect of ethyl gallate in isolated rings of superior mesenteric artery of rats, as well as to evaluate its anticoagulant and antiplatelet action. Ethyl gallate demonstrated an endothelium-dependent vasorelaxant and antioxidant effect that was inhibited by the presence of NG-nitro-L-arginina-metil ester (L-NAME) - (100 μmol L-1) or 1H[1,2,3]-oxadiazolo-[4,3-a]-quinoxalin-1ona (ODQ) - (10 μmol L-1). Arterial rings stimulated with angiotensin II (0.1 μmol L-1) had the formation of superoxide anions, analyzed by fluorescence microscopy, reduced by the presence of the gallic derivative. These results demonstrate the ability of ethyl gallate to cause vasorelaxation by activating the eNOS/NO/CGs pathway and to antagonize the pro-oxidant effect of angiotensin II in isolated rat mesenteric artery. In the evaluation of the anticoagulant and antiplatelet activity of ethyl gallate, the rats were distributed into five different groups: control group, ethyl gallate 5 mg.kg-1 group, ethyl gallate 50 mg.kg-1 group, enoxaparin 5 mg.kg-1 group, and ethyl gallate 5 mg.kg-1 + enoxaparin 5 mg.kg-1 group. The data demonstrate that ethyl gallate has an antiplatelet effect by inhibiting aggregation upon stimulation with ADP and, although it does not demonstrate a direct effect on plasma coagulation, it can potentiate the action of enoxaparin. Corroborating these results, ethyl gallate significantly reduces the occlusion time in the carotid artery treated with ferric chloride, as well as presenting a synergistic effect in animals treated concomitantly with enoxaparin. In conclusion, it can be highlighted that ethyl gallate showed relevant vasorelaxant and antioxidant potential and showed antithrombotic action and its possible usefulness in combination with other anticoagulants for the treatment of thrombotic disorders. It was also possible to demonstrate its promising antiplatelet activity with possible therapeutic application.